Optimization of Aquatic-Terrestrial Ecosystem in Relation to Soil Nitrogen Status for the Cultivation of Fish and Aquatic Food Crops of the Indian Subtropics - A.M. Puste; D.K. Das (The Scientific World Journal)
A case study was undertaken during wet and postwet seasons to improve the perennial and alternate submerged saucer-shaped ponded lands (tal and semi-tal lands) in the coasts and northeastern plains of the Indian subtropics through pisciculture and cultivation of starch- and protein-rich aquatic food crops like water chestnut (Trapa bispinosa Roxb.) and makhana or fox nut (Euryale ferox Salisb.). The study revealed that the physico-chemical properties of soils (pH, organic C, organic matter, available N, P, and K) as well as quality of water (pH, EC, BOD, COD, CO3+, HCO3, NO3-N, SO4-S, and Cl), growing fish, makhana, and water chestnut was remarkably influenced by different moisture regimes and exhibited a significant improvement of soil health. The amount of organic C, available N, P, and K content were found significantly highest in the treatment where makhana was grown under alternate flooding and drying situation with a depth >2 m as compared to other treatments. Such enrichment of soil fertility, particularly in available N and P content, might be due to the accumulation of considerable amounts of biomass and fish excreta and their subsequent decomposition in situ in the soils. Therefore, the present study suggests that the N-enriched soil may effectively be utilized further for growing subsequent arable crops surroundings during summer season, which not only saves the amount of applied N fertilizer but also increases the apparent N efficiency with simultaneous increase in yield, and would benefit the farmers in this region.